Macrophages as biomarkers in BCG treatment response in bladder cancer - Oliveira, Daniela (2013)
Bladder cancer is a common urologic cancer and the majority has origin in the urothelium. Patients with intermediate and high risk of recurrence/progression bladder cancer are treated with intravesical instillation with Bacillus Calmette-Guérin, however, approximately 30% of patients do not respond to treatment. At the moment, there are no accepted biomarkers do predict treatment outcome and an early identification of patients better served by alternative therapeutics. The treatment initiates a cascade of cytokines responsible by recruiting macrophages to the tumor site that have been shown to influence treatment outcome. Effective BCG therapy needs precise activation of the Th1 immune pathway associated with M1 polarized macrophages. However, tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype, either immunosuppressive or angiogenic, that interfere in different ways with the BCG induced antitumor immune response. The M2 macrophage is influenced by different microenvironments in the stroma and the tumor. In particular, the degree of hypoxia in the tumors is responsible by the recruitment and differentiation of macrophages into the M2 angiogenic phenotype, suggested to be associated with the response to treatment. Nevertheless, neither the macrophage phenotypes present nor the influence of localization and hypoxia have been addressed in previous studies. Therefore, this work devoted to study the influence of TAMs, in particular of the M2 phenotype taking into account their localization (stroma or tumor) and the degree of hypoxia in the tumor (low or high) in BCG treatment outcome. The study included 99 bladder cancer patients treated with BCG. Tumors resected prior to treatment were evaluated using immunohistochemistry for CD68 and CD163 antigens, which identify a lineage macrophage marker and a M2-polarized specific cell surface receptor, respectively. Tumor hypoxia was evaluated based on HIF-1α expression. As a main finding it was observed that a high predominance of CD163+ macrophage counts in the stroma of tumors under low hypoxia was associated with BCG immunotherapy failure, possibly due to its immunosuppressive phenotype. This study further reinforces the importance the tumor microenvironment in the modulation of BCG responses.